СТАТУС ИСТОРИЧЕСКОГО В МАКЕДОНСКОМ РОМАНЕ (Filološke studije, 2019)
Taking into consideration various aspects of the relation between the history and the novel, based upon several different approaches, this paper presents 3 general models of identification of the proposed relation in the frames of the Macedonian novelistic production: - thematic focus on the past as a possibility to reconstruct the historical occurrences and thus, to remember them; - thematic focus on the past as a possibility to reveal the «dark spots» in the historical occurrences; - thematic focus on the past with an ironical code or towards the marginalized and anonymous persons from the past. The paper uses particular examples of the novels by Janevski, Popov, Boshkovski, Maleski, Georgievski, Mickovich, Lafazanovski and Andonovski to present the change of the awareness of the role and the function of the history and the historical in the novel: as a reconstruction of the objective occurrences, as a possibility for perception of the conditions that the history can’t present and as a possibility to perceive the history in a new, contemporary context.